A tagging polymorphism in fat mass and obesity-associated (FTO) gene is associated with sepsis status in children - Jabandziev Petr; Hubacek Jaroslav Alois; Michalek Jaroslav; Jouza Martin; Papez Jan; Pecl Jakub; Slaba Katerina; Slaby Ondrej; Urik Milan; Aulicka Stefania; Kunovsky Lumir; Michalek Jaroslav; et al. (Sciendo, 2024)
Sepsis is one of the most common causes of death in patients admitted to intensive care units (ICUs). The development of sepsis is significantly influenced by genetic predisposition. In this study, we highlight a potential association between a variant of the fat mass and obesity-associated (FTO) gene and risk of sepsis in children and adolescents.